2016
DOI: 10.1038/srep24226
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function Mutation in PMVK Causes Autosomal Dominant Disseminated Superficial Porokeratosis

Abstract: Disseminated superficial porokeratosis (DSP) is a rare keratinization disorder of the epidermis. It is characterized by keratotic lesions with an atrophic center encircled by a prominent peripheral ridge. We investigated the genetic basis of DSP in two five-generation Chinese families with members diagnosed with DSP. By whole-exome sequencing, we sequencing identified a nonsense variation c.412C > T (p.Arg138*) in the phosphomevalonate kinase gene (PMVK), which encodes a cytoplasmic enzyme catalyzing the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 24 publications
(31 reference statements)
3
34
0
Order By: Relevance
“…We were pleased to read the recent publications by Wang et al . and Li et al ., whose findings support and supplement our previous findings .…”
Section: Updating the Mutations Of Pmvk Identified In Porokeratosissupporting
confidence: 89%
See 1 more Smart Citation
“…We were pleased to read the recent publications by Wang et al . and Li et al ., whose findings support and supplement our previous findings .…”
Section: Updating the Mutations Of Pmvk Identified In Porokeratosissupporting
confidence: 89%
“…and Li et al ., whose findings support and supplement our previous findings . Using whole‐exome sequencing, the nonsense variation c.412C>T (p.Arg138*) in PMVK was also identified in two Chinese families with porokeratosis . In that study, both Figure b and supplementary Figure 1b3 showed the clinical phenotypes of classic PM, not disseminated superficial porokeratosis.…”
Section: Updating the Mutations Of Pmvk Identified In Porokeratosissupporting
confidence: 87%
“…Recently, heterozygous germline mutations of the mevalonate pathway genes MVK (MIM 251170), PMVK (MIM 607622), MVD (MIM 603236), and FDPS (MIM 134629) were identified in familial and sporadic porokeratosis, while 1 study identified germline mutations in SLC17A9 (MIM 612107) in familial DSAP. [4][5][6][7] Mosaicism refers to the presence of genetically distinct cells within an organism that result from postzygotic mutation. 8 The patterning and appearance of cutaneous mosaic disorders are largely determined by mutation timing, its pathophysiological effects, and by the affected cutaneous progenitor cells.…”
mentioning
confidence: 99%
“…Porokeratosis is considered to be a premalignant condition, and higher rates of skin cancer have been described in linear and large plaques, with the most common malignancy being squamous cell carcinoma (Sasson and Krain, 1996). Recent studies have identified heterozygous germline mutations of the mevalonate pathway genes MVK, MVD, PMVK, and FDPS (which encode the corresponding enzymes) in familial as well as sporadic porokeratosis (Wang et al, 2016;Zhang et al, 2015Zhang et al, , 2012.…”
mentioning
confidence: 99%